Exosomes derived from Panax notoginseng promote osteogenic differentiation of rBMSCs via the PI3K/AKT signaling pathway - Wu, Nan; Zhang, Lintao; Guo, Hua (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to investigate the effect of exosomes derived from Panax notoginseng on the osteogenic differentiation of rat bone marrow-derived mesenchymal stem cells (rBMSCs) and to elucidate the underlying intracellular signaling mechanisms.MethodsExosomes from Panax notoginseng were isolated using differential centrifugation combined with sucrose density gradient centrifugation. The morphology of the exosomes was characterized by transmission electron microscopy (TEM), while size distribution and concentration were determined via nanoparticle tracking analysis (NTA). rBMSCs were isolated and identified by flow cytometry, and the uptake of fluorescently labeled Panax notoginseng exosomes by rBMSCs was confirmed using confocal microscopy. The optimal concentration of exosomes was determined using the CCK-8 assay. Osteogenic differentiation was evaluated by measuring alkaline phosphatase (ALP) activity, performing ALP staining, and conducting Alizarin Red S staining. The expression levels of osteogenic markers (collagen type I(COL1), ALP, osteopontin (OPN), and Runt-related transcription factor 2 (RUNX2)) were quantified at the mRNA (RT-qPCR) and protein (Westem blotting)levels. High-throughput RNA sequencing and bioinformatics analyses (Gene Ontology (GO),Kyoto Encyclopedia of Genes and Genomes (KEGG)) were employed to identify differentially expressed genes and enriched pathways. Key pathways were validated using specific inhibitors.ResultsExosomes derived from Panax notoginseng promote the osteogenic differentiation of rBMSCs through the activation of the PI3K/AKT signaling pathway. This study provides experimental evidence and theoretical support for the application of herbal exosomes in bone tissue engineering and the treatment of osteoporosis.ConclusionPanax notoginseng exosomes promote osteogenic differentiation of rBMSCs by activating the PI3K/AKT pathway, providing experimental evidence and theoretical support for the application of herbal exosomes in bone tissue engineering and osteoporosis treatment.